TRADISI FALIASEBAGAI MEKANISME KONTROL DALAM MENCIPTAKAN TERTIB DAN HARMONI SOSIAL: TELAAH TERHADAP TRADISI FALIAMASYARAKAT MUNA DI SULAWESI TENGGARA - basri, lao de ali (ACARYA PUSTAKA, 2018)
TRADISI FALIASEBAGAI MEKANISME KONTROL DALAM MENCIPTAKANTERTIB DAN HARMONI SOSIAL: TELAAH TERHADAP TRADISIFALIAMASYARAKAT MUNA DI SULAWESI TENGGARALa Ode Ali Basri11 Jurusan Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Halu Oleo Kendari.*) Koresponden: La Ode Ali Basri, Jurusan Ilmu Sejarah Fakultas Ilmu Budaya, UniversitasHalu Oleo Kendari, Sulawesi Tenggara Indonesia, Tlp: 081341797344, E-mail:basri.uho74@gmail.comABSTRACTThis study studied falia ( taboo) in Muna community which becomes a controlmechanism in creating social order and harmony. The result of the study shows that thefaliatradition is a custom and belief practiced by Muna community on things that cannot be doneor spoken or undesirably unwanted to be done or spoken by someone or a group of peoplesince it is considered a taboo. In the falia tradition there are universal human values, suchas moral teaching and ethics, respecting and appreciating the result that is communicatedindirectly. The teaching or moral messages and ethics the the principle is a form ofcharacter education since it develops a person’s behavior in order he or she always speakpolitely, behaves ethically, has good manners and good ethics. The moral messages in thefalia tradition is among others implicitly stated in falia that is related to ethics, motivationto lead a successful life through hard work and accomplished work, and falia whichrecommends the need to appreciate other’s works.Keywords: Falia, control mechanism and social order.